A.
In the first generation we have 2 ancestors.
In the second generation we have 4 ancestors or
![2^{2}](https://tex.z-dn.net/?f=2%5E%7B2%7D%20)
ancestors.
In the third generation we have 8 ancestors ot
![2^{3}](https://tex.z-dn.net/?f=2%5E%7B3%7D%20)
ancestors.
We can see that each succesive generation has two times more members. The sum is:
![2+4+8+16+...+ 2^{40}](https://tex.z-dn.net/?f=2%2B4%2B8%2B16%2B...%2B%202%5E%7B40%7D%20)
To calculate number of ancestors we can use formula <span>for the sum of a geometric sequence. Geometric sequence is sequence of numbers that differ by a certain factor. This factor is called ratio. Formula is:
</span>
![S= a_{1} * \frac{1- r^{n} }{1-r}](https://tex.z-dn.net/?f=S%3D%20a_%7B1%7D%20%2A%20%5Cfrac%7B1-%20r%5E%7Bn%7D%20%7D%7B1-r%7D%20)
<span>Where:
S -> sum
a1 -> first member of a sequence
r -> ratio
n -> number of elements
For this question:
a1 = 2
r = 2
n = 40
</span>
![S= 2* \frac{1- 2^{40} }{1-2} =2 199 023 255 550](https://tex.z-dn.net/?f=S%3D%202%2A%20%5Cfrac%7B1-%202%5E%7B40%7D%20%7D%7B1-2%7D%20%3D2%20199%20023%20255%20550)
<span>
b.
1 generation = 25 years
40 generations = 40 * 25 = 1000 years
c.
Total number of people who have ever lived = </span>
![10^{10}](https://tex.z-dn.net/?f=10%5E%7B10%7D%20)
Number of ancestors in 40 generations =
![2.2*10^{12}](https://tex.z-dn.net/?f=2.2%2A10%5E%7B12%7D%20)
The number of ancestors is greater than total number of people who have ever lived. This means that not all ancestors were distinct and that in each generation both men and women had children with more than one partner.
Answer:
1/4 > 1/5
Step-by-step explanation:
think of a candy bar. if you split it into 4 parts the prices would be bigger than if u had to break it into 5 parts. also remember that the smaller number eats the bigger number so the sign would be towards the 1/4
The standard equation of a circle is given by:
(x-a)²+(y-b)²=r²
where:
(a,b) is the center and r is the radius.
Given that (a,b) is (-8,-3) and r=2 units
then the equation of the circle will be:
(x-(-8))²+(y-(-3))²=2²
simplifying the above we get:
(x+8)²+(y+3)²=4
Www. is your answer. Hope I could help
Your answer is -8.5
Can you mark as brainiest??
Please